The occurrence of PAHs and faecal sterols in Dublin Bay and their influence on sedimentary microbial communities. Issue 1 (15th May 2016) - Murphy, Brian T.; O'Reilly, Shane S.; Monteys, Xavier; Reid, Barry F.; Szpak, Michal T.; McCaul, Margaret V.; Jordan, Sean F.; Allen, Christopher C.R.; Kelleher, Brian P.
Abstract: The source, concentration, and potential impact of sewage discharge and incomplete organic matter (OM) combustion on sedimentary microbial populations were assessed in Dublin Bay, Ireland. Polycyclic aromatic hydrocarbons (PAHs) and faecal steroids were investigated in 30 surface sediment stations in the bay. Phospholipid fatty acid (PLFA) content at each station was used to identify and quantify the broad microbial groups present and the impact of particle size, total organic carbon (%TOC), total hydrogen (%H) and total nitrogen (%N) was also considered. Faecal sterols were found to be highest in areas with historical point sources of sewage discharge. PAH distribution was more strongly associated with areas of deposition containing high %silt and %clay content, suggesting that PAHs are from diffuse sources such as rainwater run-off and atmospheric deposition. The PAHs ranged from 12 to 3072 ng/g, with 10 stations exceeding the suggested effect range low (ERL) for PAHs in marine sediments. PAH isomer pair ratios and sterol ratios were used to determine the source and extent of pollution. PLFAs were not impacted by sediment type or water depth but were strongly correlated to, and influenced by PAH and sewage levels. Certain biomarkers such as 10Me16:0, i 17:0 and a 17:0 were closely associated with PAH polluted sediments, while 16:1ω9, 16:1ω7c, Cy17:0, 18:1ω6, i 16:0 and 15:0 all have strong positive correlations with faecal sterols. Overall, the results show that sedimentary microbial communities are impacted by anthropogenic pollution. Highlights: PLFA biomarkers indicate that microbial populations are impacted by the type anthropogenic pollution. Sterol biomarkers reveal the 'fingerprint' of historical sewage discharge from point sources. PAH accumulation is dictated by depositional processes in the bay. 10 stations exceed the suggested effect range low (ERL) for PAHs.